Pembuatan Trainer Tempat Sampah Otomatis Guna Menyiasati Masalah Sampah Di Lingkungan Masyarakat - Hans Perdana Putra; Syamsudin Nur Wahid (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2019)
Ngadirejo Village is a safe and comfortable village with the majority of the population working in agriculture and animal husbandry. However, on the other hand, public awareness and concern for handling waste is still lacking. Concerns about the waste problem can be reduced by increasing public awareness to treat waste properly and correctly. Therefore, the author tries to make a tool that is an Automatic Trash Place so that the community members are not reluctant to throw garbage in the trash. They do not need to touch the lid of the trash, to open it only need to hold hands and automatically the trash can will open. Trash cans are made by modifying existing bins. Swivel-covered bins are connected by servo motors and ultrasonic and infrared sensors which are controlled by the Arduino Uno microcontroller kit. This trash can can function properly and be used properly by the community. The results of this research are that the trash can can respond to garbage that is 20 cm away quickly and the trainer is used by students of the electrical engineering study program at Balitar Islamic University as a learning medium.